REASSESSING GIFTED STUDENTS FROM ELEMENTARY INTO SECONDARY EDUCATION - Johnson, Emily (Acta Scientiae et Intellectus, 2024)
The identification of gifted students is a complex, broad topic without a standard state or federal process. Furthermore, once students are identified there lacks a consensus in the educational community regarding how gifted students should be reassessed throughout their educational careers, if it should be done at all. This paper explores how students are identified, how and why students may regress or progress through their giftedness from elementary through secondary school, and why reassessment is necessary. The regression and stagnation topics of diminishing motivation, the need for adult connections, mentoring, counseling and reasons for gifted dropouts are discussed as well as the ways gifted programs can encourage student growth through motivation, the use of technology, and effective interventions.